1000 tips for landscape architects - Quartino, Daniela Santos (Bercelona LOFT Publication, 2011)
100 landscape architects offer their expertise on various facets of landscape architecture, not limited to just an extensive knowledge of the botanical aspects: choosing plants, trees, and shrubs that best thrive in a specific region, designs of patios, fences, rock beds, pavers, stone work, gazebos, pergolas, pool decks and water features (fountains, waterfalls, pools, spas, and ponds with fish). This book offers real professional knowledge to those who are not necessarily born with a green thumb but show an interest in landscape with design, advice, and do-it-yourself landscape recommendations, all richly illustrated.
Keywords: ARCHITECTURE; LANDSKAB; LANDSCAPE ARCHITECTURE (AR-LA)